2018
DOI: 10.1089/pho.2017.4301
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Spectroscopy as a Tool for the Assessment of Liver Samples with Several Stages of Fibrosis

Abstract: With this study, it is concluded that fluorescence spectroscopy can be used as a complementary tool for the assessment of liver fibrosis in liver tissue samples, which sets the stage for subsequent clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nevertheless, a lesser invasive application of this tool in vivo is possible using endoscopic instrumentation, we have previously reported the use of DRS as an effective tool to evaluate the optical differences among normal and fibrotic liver both in an animal model of hepatic chronic disease 12 and in paraffin preserved human samples. 31 Other reports support DRS use in assessing liver pathologies. [14][15][16][17]24,32 NAFLD is an increasingly common hepatic disease worldwide, with a spectrum that comprises from simple steatosis, a benign lipid accumulation in the hepatic parenchyma; through NASH, which besides steatosis, includes inflammation and features of oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, a lesser invasive application of this tool in vivo is possible using endoscopic instrumentation, we have previously reported the use of DRS as an effective tool to evaluate the optical differences among normal and fibrotic liver both in an animal model of hepatic chronic disease 12 and in paraffin preserved human samples. 31 Other reports support DRS use in assessing liver pathologies. [14][15][16][17]24,32 NAFLD is an increasingly common hepatic disease worldwide, with a spectrum that comprises from simple steatosis, a benign lipid accumulation in the hepatic parenchyma; through NASH, which besides steatosis, includes inflammation and features of oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…Correlation studies have been successfully employed previously either to inspect the applicability of the technique to be tested by comparing it with reference method or to measure the relationship between 2 variables . Fabila‐Bustos et al have recently utilized fluorescence spectroscopy as an analytical tool to discriminate different stages of fibrosis using liver tissue samples. Furthermore, they have reported a correlation between the shape of the fluorescence spectrum and level of liver fibrosis, and concluded that fluorescence spectroscopy could serve as a complimentary tool for clinical assessment of fibrosis.…”
Section: Discussionmentioning
confidence: 99%